Corporate Social Responsibility - Understanding the Concept, Challenges and its Present Status in India - Gulati, Gagandeep Kaur (Gyan Management Journal, 2014)
In the present state the world around is surrounded with numerous problems related to environment. Thus, now the organizations are also expected to play some role and sort out these problems. This is because business is a part of society. Though, earning more and more profits is a natural phenomenon of every business unit. However, profits cannot alone be determined as the goals in seclusion with some other considerations. The Economic Activities also entail with them, an ethical foundation which offers equal amount of importance to the people, the environment and broader social considerations as well. Business comes in contact with various groups of society such as owners, employees, customers, government, suppliers etc. The responsibility of business, which includes satisfaction of these parties along with the owner, is called social responsibility of business. The importance of CSR is being recognized; with so many companies coming into limelight, which conduct their operations in a responsible manner. The activities that we undertake or we do not undertake today, will definitely influence our future generations. We need to understand that with every conscious efforts, we can make the world for them a better place to live. That’s what CSR is about." The present paper describes the Concept and challenges of CSR with special relevance to India and the steps being taken by various organization towards making a better Environment.